Foot orthoses and gait: a systematic review and meta-analysis of literature pertaining to potential mechanisms. Issue 14 (8th December 2009) - Mills, Kathryn; Blanch, Peter; Chapman, Andrew R; McPoil, Thomas G; Vicenzino, Bill
Abstract : This article systematically reviews the available literature to improve our understanding of the physiological basis for orthoses under the kinematic, shock attenuation and neuromotor control paradigms. The propositions made under these three paradigms have not been systematically reviewed collectively, and as such, there is no single-point synthesis of this clinically relevant body of evidence and somewhat disparate findings. Our comprehensive search strategy yielded 22 papers. Under each paradigm, the role of orthoses with different design features including combinations of posting, moulding and density was analysed. Where possible, data have been pooled to provide an increased level of confidence in findings. The main findings in the kinematic paradigm were that posted non-moulded orthoses systematically reduced peak rearfoot eversion (2.12° (95% CI 0.72 to 3.53)) and tibial internal rotation (1.33° (0.12 to 2.53)) in non-injured cohorts. In the shock attenuation paradigm, it was found that non-posted moulded and posted moulded orthoses produced large reductions in loading rate and vertical impact force when compared with a control and to a posted non-moulded orthosis. The neuromotor control paradigm seems to be the least conclusive in its outcome. Based on our review, this paper concludes with rudimentary guidelines for the prescription of orthosis, that sports medicine practitioners may use in their clinical decision-making process. The need for further research focusing on the role of injury, particularly in neuromotor control modification and long-term adaptation to orthoses, was highlighted.